Foregrounding the Digital Medium: Self-reference and Metareference in Video Essays - Drăgan, Cristian Eduard (Ekphrasis. Images, Cinema, Theory, Media, 2021)
This article focuses on video essays — understood as that specific subgenre of audio-visual productions that can be considered the main descendent of the essay film. Both are, in a sense, subjective explorations of certain subject matters via cinematic means — with the prime exception that video essays are mostly centred on analyses of filmic phenomena. Since another difference between these two types of productions is the very medium that they originate in, ‘inhabit’, and are propagated through — digital video and online video-sharing platforms, such as YouTube or Vimeo vs. photochemical film strip or electronic tape, and theatrical / home video releases —, I propose that one of the fundamental characteristics of video essays is a special type of foregrounding of the medium, and therefore one of its main effects on the viewers is that of eliciting a sort of medium-awareness. Starting from a semiotic definition of self-reference — as the ability of signs to point to themselves or to the sign-system that they are a part of — I propose an exploration of the ways in which certain video essays call attention to their status as digital artefacts, thus engaging with aspects of their medium and their relationship (1) with other images in general and (2) with the audience. This paper focuses on three case studies: Max Grau’s «[…] craving for narrative» lässt sich einfach nicht gut übersetzen (2016); Kevin B. Lee’s Transformers: The Premake (a desktop documentary) (2014); Gregory Guevara’s This is a video essay (2018).